The Relevance of French Language Learning to National Development in Nigeria - Odudigbo, Mercy Eghonghon; Musa, Ahmed Eleojo (NIU Journal of Social Sciences; Vol 10 No 1 (2024): NIU Journal of Social Sciences, Vol. 10 No. 1, March 2024DO - 10.58709/niujss.v10i1.1807, 2024)
Language is an integral part of a society and its role in national development cannot be undermined. Since its acceptance as the second official language by Nigerian government, French language has not been given immense attention like English language. This has affected its acquisition and its function as the country’s second official language. Its low acquisition has also affected the country’s bilateral relationship not only with France but also with other francophone countries especially in Africa hence preventing some aspects of socio-economic development. This article examines the relevance of French language learning to national development in Nigeria. It adopts an explorative approach to depict the importance of French language acquisition and Its role in national development. It anchors its analysis on the Nigerian education system to expose why the teaching of French language must be accorded immense importance. The article revealed that Nigeria has the great potential of achieving its development policy if French language becomes as functional as English language. It also recommends among others that the learning of French language should be encouraged and supported in schools for easy acquisition by learners. Keywords: Development Education, French, Language, Nigeria, Schools